Less Competition, More Meritocracy? - Fang, Dawei; Noe, Thomas (Journal of Labor Economics, 2022)
Uncompetitive contests for grades, promotions, retention, and job assignments, which feature lax standards and limited candidate pools, are often criticized for being unmeritocratic. We show that when contestants are strategic, lax standards and exclusivity can make selection more meritocratic. When many contestants compete for a few promotions, strategic contestants adopt high-risk strategies. Risk-taking reduces the correlation between performance and ability. Through reducing the effects of risk-taking, “Peter principle” promotion policies, which entail promoting some contestants that are unlikely to be worthy, can increase the overall correlation between selection and ability and thus further meritocracy.